PENGARUH PEMBERIAN INTENSIF TERHADAP PRODUKTIVITAS KINERJA KARYAWAN CV. WALLET GROUP BUAY MADANG OGAN KOMERING ULU TIMUR - Iin Afrina, Oktariansah; Afrina, Iin (Jurnal Trisna Riset, 2025)
CV. Wallet Group Buay Madang Ogan Komering Ulu Timur is facing problems in providing intensive services which have not been fully implemented optimally which has an impact on low productivity of employee performance. Problems faced by CV. Wallet Group Buay Madang Ogan Komering Ulu Timur in achieving its goals is the low performance of employees in carrying out their duties which is caused by a lack of intensive support from the leadership. This research aims to analyze the effect of intensive provision on employee performance productivity. The data collection techniques used were observational literature study, question and answer, questionnaires and documentation. Based on the results of observations, it shows that there is a very strong relationship between these two variables. To determine the relationship between existing variables, correlation coefficients are used and calculations with conservative standards include very strong correlations. This means that intensive provision of employee performance productivity is good because it has a very strong correlation and the percentage level obtained was 75.17% while 24.83% was influenced by other factors that were not researched. From the calculation above, the calculated result is 4,920 with a confidence level of 95%, which means the error rate is 5%, which is 1 count greater than the t table, namely, 4,920 1,860, this means that Ha is accepted and rejected, thus the previously formulated hypothesis can be accepted. The conclusion drawn is that intensive provision from leaders has a big influence on increasing employee productivity and performance motivation. The advice given is for leaders to be active in the work environment and provide intensive work that suits the quality of employees’ work to achieve maximum results.